KOREOGRAFI TARI PASISIA MAIMBAU DI SANGGAR SAN ALIDA PAINAN KABUPATEN PESISIR SELATAN - Hayati, Yashirly; Asriati, Afifah (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe and analyse the choreography of the Pasisia Maimbau Dance at Sanggar San Alida, Painan, South Coast Regency. The type of research is qualitative with a descriptive method. The object of the study is the Pasisia Maimbau Dance, a creation by Erviela Desarta. The main instrument in this research is the researcher, assisted by a camera, writing tools, and a recording device. Data collection techniques used include literature review, observation, interviews, and documentation. The collected data are then analysed through the stages of data reduction, data presentation, and drawing conclusions. The results show that the choreography process of the Pasisia Maimbau Dance goes through three stages: exploration, improvisation, and formation. The dance ideas are inspired by the natural beauty of the South Coast, expressed in dynamic and expressive movements. The choreography of this dance includes movement elements, floor patterns, dramatic design, group composition, accompanying music, and dance props. The dance is performed by 5–6 female dancers, with movements derived from basic Minangkabau dance steps that have been creatively adapted. The performance consists of three sections: a soft opening, a dynamic main section, and an energetic closing. The accompanying music combines traditional and modern instruments such as talempong, gandang, flute, keyboard, and drums, accompanied by live singing. The costumes support the dance's character, with a shawl as a symbolic element representing the sea waves. Overall, the choreography of Tari Pasisia Maimbau demonstrates the choreographer's creativity and innovation in developing a dance creation based on Minangkabau tradition.